IMPLEMENTASI KEBIJAKAN PENGEMBANGAN MANAJEMEN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) KOTA SALATIGA - Eirene Laura Juwita Herawati; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study aims to deeply analyze the implementation of the Electronic-Based Government System (SPBE) policy in Salatiga City and to identify the supporting and inhibiting factors in its execution. SPBE is a strategic initiative by the Indonesian government to achieve clean, effective, transparent, and accountable governance through the integrated use of information and communication technology (ICT). Using a descriptive qualitative approach with a case study method, this research explores the implementation complexities behind quantitative achievements. Data were collected through in-depth interviews with key local government officials, non-participant observation, and document analysis of SPBE-related policies. The findings reveal a paradox: although Salatiga City achieved a